Discretionary Loan Loss Provision Behaviour and Banks’ Liquidity Creation - Sanzid A. Haq,; Dung Viet Tran,; M. Kabir Hassan, (Asian Academy of Management Journal of Accounting and Finance, 2019)
Over the last 30 years, liquidity creation has become a USD12.3 trillion business and large banks seem to have all but secured their indelible footprint in the banking industry. Moreover, over a 24 years period (1984 through 2008) big banks have managed to turn their 76% dominance to a prodigious 86% footprint, while the medium and small banks lost ground in the wake. So, looking for ways to create liquidity has become an existential crisis for non-large banks also an avenue for larger banks to maintain their leads. In an effort to find an innovative way to create liquidity, banks have turned to tools that lend themselves to be manipulated at discretion without material consequence to the rest of the business. Discretionary loan loss provision (DLLP) has become such a tool. Using a large sample of the U.S. bank holding companies from the first quarter of 2000 through the fourth quarter of 2015, we explore the relationship between discretionary loan loss provision and liquidity creation and find that, perhaps much to the dismay of some banks, earning manipulation through a tool like DLLP has a negative impact on liquidity creation. Moreover, this impact is indiscriminate regardless of whether the banks are facing an economy that is marred by financial crisis or otherwise. Our findings stand the test of various sensitivity tests to demonstrate their robustness and consistent with prior findings in the literature.